Continuous Control in Bacterial Regulatory Circuits - Batchelor, Eric (American Society for Microbiology, 2004)
We show that for two well-characterized regulatory circuits in Escherichia coli, Tn10 tetracycline resistance and porin osmoregulation, the transcriptional outputs in individual cells are graded functions of the applied stimuli. These systems are therefore examples of naturally occurring regulatory circuits that exhibit continuous control of transcription. Surprisingly, however, we find that porin osmoregulation is open loop; i.e., the porin expression level does not feed back into the regulatory circuit. This mode of control is particularly interesting for an organism such as E. coli, which proliferates in diverse environments, and raises important questions regarding the biologically relevant inputs and outputs for this system.